The Threat Posed by Educated Individual - Abubakar, Anwar; Yahya, Muhammad (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Knowledge is a great gift that places humans in a noble position in the sight of Allah SWT. However, from an Islamic perspective, knowledge is not always synonymous with salvation and glory if it is not accompanied by faith, sincerity, and practice. This article examines the concept of threats to people of knowledge from the perspective of thematic hadith (al-hadith al-maudhu'i), by examining the hadiths of the Prophet Muhammad SAW that emphasize the dangers of knowledge that is not practiced, misused, or used as a means for worldly interests. This research uses a library study method with a thematic approach to relevant hadith. The results of the study indicate that threats to people of knowledge encompass spiritual, moral, and social aspects, and have serious implications for religious and professional life.